A Cross-Sectional Examination of the Writing of Students with Visual Impairments. (May 2019) - Savaiano, Mackenzie E.; Hebert, Michael
Introduction: Not much is known about the writing skills of students with visual impairments, and this research is often limited to subgroups of the population or subskills. A more comprehensive approach to research on the writing skills of students with visual impairments is needed. Methods: Researchers used a cross-sectional design to examine the writing of students with visual impairments in Nebraska, attempting to include as many students as possible aged from 4 to 21 years. Fifty students participated. All students were given the Essay Composition subtest of the Wechsler Individualized Achievement Test (third edition), with modified instructions. Essays were scored on number of words, essay elements, and mechanics. Descriptive statistics and statistical comparisons of groups are provided. Results: Mean scores of the overall sample and subgroups fell within the average range when compared to normative samples. There were no statistical differences between students who were blind and students with low vision and no statistical differences between writing modality. There were statistical differences between students with multiple disabilities and others. Results suggest substantial heterogeneity in the sample. Discussion: Results suggest some students with visual impairments write as well as do their sighted peers. These results are complicated by heterogeneity and do not imply anything about the writing ability of individual students. Implications for practitioners: Teachers should avoid making assumptions about the writing potential of specific students. Students with visual impairments in this study scored comparably to a normative sample, and students with multiple disabilities may be able to participate in writing activities in a variety of ways.